(untitled) (Medico Legal Update, 2021)
Socio-cultural elements may affect someone to follow or leave a behavior. Cultural values in the Bima District-West Nusa Tenggara Province community that are in line with health behavior are the cultural values called “Maja Labo Dahu/MLD”, “Maja” means self-aware and “dahu” means carefulness. This study aims to determine the effect of integrating the cultural value of “MLD” and health education toward the intention of high school student to stop smoking in Bima district . This study is a quasy experiment with pre-post-test with control group design with purposiv sampling on 60 students of 5 Senior High School in Bima district. Self report was used to analyze the intention to stop smoking. Data analysis was examined by using Pairred T-Test. The results showed 86.7% had strong intention to stop smoking and 13.3% had weak intention. The mean standard pre-post deviation in the treatment group was 4,633 ± 8,046 with a p-value <0.001. It can be concluded that there was a significant effect of interventions integrating MLD cultural values and health education toward the intention of student to stop smoking. Therefore, “Smoking session” efforts are required by considering elements of local culture and family resources.